Application Of Website-Based Men’s Fashion Purchase Application (Blibli Shionpri) - Aidin Fajar Shodiq Agusman; Cindy Taurusta (Universitas Muhammadiyah Sidoarjo, 2022)
The use of smartphone from year to year is getting more dan more enthusiasts and will continue to increase everyyear, this is due to the increasingly rapid development of the times. The existence of social media features that are easy to accessand offered with their respective benefits and goals will centainly make it easier for users to communicate and find out updatedinformation, one of which is in conducting online buying and selling transactions. Fashion is one of the things that is widelyfollowed by its development, buying fashion online aims to make buying and selling transactions easily and comfortably withoutany geographical constraints, saving energy, shortening time and being cheap, easy to find the desired item, and establishinggood cooperative relationships. Both between the seller and the buyer. However, there are several problems that are oftenexperienced by users of online buying and selling transaction services. This has a solution with a strong information and securitysystem in order to provide more satisfaction for users of online buying and selling services.